PROCESS OPTIMIZATION OF SOLVENTS ASSISTED POLYETHYLENE WASTE RECYCLING - Abdullahi, Salisu; Sokoto, A. M.; Muhammad, C.; Umar, A. (FUDMA Journal of Sciences, 2023)
The global production and consumption of plastics has been increasing continuously. However, disposing of plastic wastes in landfill is becoming undesirable due to poor biodegradability. The re-utilization of plastics together with the development of green technologies is mandatory, hence chemical recycling offers a promising alternative as a potential for plastics to maintain their original properties. The scope of this research is focused on the recycling of plastic waste by the chemical dissolution method to optimize the reaction variables in the dissolution/precipitation method using a statistical experimental design. Optimization of the recycled plastics was done using response surface methodology based on box Behnken design. The optimum yield of the recovered plastic 93.4% was achieved at a temperature of 300C, a residence period of 30min and a solvent/non-solvent ration of 1:2 v/v. The mechanical and physical properties of the recovered plastics revealed similar value to that of the virgin polymer. The FTIR spectrum of the recycled plastics shows a less significant structure alteration when compared with the spectra of the virgin polymers. Similarly, the thermal stability of the recycled plastics determined using thermogravimetric analysis (TGA) shows a less significant difference when compared with the reported thermal stability of the virgin polymers. Therefore, the study infers that chemical recycling (dissolution/precipitation) can be an appreciable option for getting rid of waste plastics in the environment as well as providing feedstock for the reproduction of plastics.
Keywords: dissolution; precipitation; polyethylene; solvents; optimization; recycling